Quantification of Curcumin Obtained from Supercritical Carbon Dioxide Extraction of Curcuma domestica Valet. Rhizomes - Sharma D.; Said P.P.; Singh R.S.; Rai B.N. (My University, 2025)
Background: Curcumin is well known bioactive compound available in Curcuma domestica Valet i.e. turmeric. The research work was carried with intention to get maximum yield of medicinally active constituents (Curcumin) of Curcuma domestica Valet. rhizomes through supercritical fluid extraction. Methods: The experiments were conducted in the year 2013-14. Process parameters namely pressure, temperature, flow rate and particle size were optimized using a Taguchi method. During investigation, L9 orthogonal array experimental design was followed. Result: The optimized values of pressure, temperature, flow rate and particle size obtained were 35 MPa, 40◦C, 25 g/min and 0.246 mm, respectively. Significant improvement in the yield of curcumin and extract was obtained under optimum operating conditions. © 2023 Agricultural Research Communication Centre. All rights reserved.